The Relationship Between Sleep Quality and Body Mass Index (BMI) in Unjani Medical Faculty Students - Dinar Mutiara; Daswara Djajasasmita; Sesi Pratiwi (Sean Institute, 2025)
Excess weight is a major public health problem with high prevalence rates increasing every year. Excess weight in adults has increased 10-fold over the past four years. Decreased sleep time is a factor that plays a role in increasing weight/obesity. This study aims to determine the quality of sleep in students with normal body mass index and excess weight. This study is a analytical study of medical faculty students of General Achmad Yani University class of 2020 with consecutive sampling method. Measurement of sleep quality was carried out through filling out the Pittsburgh sleep quality index (PSQI) questionnaire and measurement of body mass index was carried out by measuring body weight and height analyzed by the Chi Square test. Of the 88 research subjects showed that in the group of students with normal body mass index there were 37 students with poor sleep quality (78.7%) and 10 students with good sleep quality (21.2%). In the group of students with excess body mass index there were 30 students with poor sleep quality (73.1%) and 11 students with good sleep quality (26.8%). From the results of the analysis, it was found that there was no relationship between the quality of sleep of students and body mass index (p = 0.542). Decreased sleep time can lead to poor sleep quality which can cause imbalances in the hormones ghrelin and leptin. From the results of this study, other factors that can cause disturbed sleep are health problems and psychological disorders.